Perubahan Penggunaan Lahan dan Faktor Penyebab Urban Sprawl di Wilayah Peri-Urban Kabupaten Klaten - Vania Rizky Nurrahmah Azizah; Lutfia Nursetya Fuadina (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2026)
Abstract: Java Island's urbanization has reached a critical stage, with population densities expanding to the suburbs in addition to the city center. One of the most vulnerable locations under fast demographic pressure is Klaten Regency, which is a part of the Surakarta Raya (Subosukawonosraten) supporting area. This condition is consistent with the growing demand for developed land, which has led to urban sprawl in Klaten Regency's northern part, especially in the districts of Ceper, Delanggu, and Polanharjo. As a result, a significant amount of agricultural land has been transformed into developed regions. The purpose of this study is to determine the causes of urban sprawl as well as shifts in agricultural land use to built-up regions. This study uses a quantitative descriptive research method with a spatial approach by overlaying land use imagery from 2017 and 2025 collected from Sentinel 2 imagery, followed by Geographically Weighted Regression (GWR) analysis. According to the overlay data, urban sprawl has resulted in a significant rise in built-up areas of 375,02 ha (37.95%). The GWR analysis's findings show that accessibility, population growth, and the proportion of agricultural land in the study area are the main causes of urban sprawl. In industrial regions like Ceper Sub-District, land conversion is more significantly impacted by demographic pressure. Meanwhile, the accessibility and agricultural land area variables have a stronger influence in Polanharjo and Delanggu Sub-Districts. Keywords: Urban Sprawl, Land Use Change, Causal Factors Abstrak: Urbanisasi di Pulau Jawa telah mencapai titik krusial, di mana pemusatan aktivitas penduduk tidak hanya di pusat kota, melainkan menjalar ke wilayah pinggiran kota. Kabupaten Klaten sebagai bagian dari kawasan penunjang Surakarta Raya (Subosukawonosraten) menjadi salah satu titik paling rentan mengalami tekanan demografis yang pesat. Hal ini sejalan dengan meningkatnya kebutuhan lahan terbangun yang memicu fenomena urban sprawl di wilayah utara Kabupaten Klaten, khususnya di Kecamatan Ceper, Delanggu, dan Polanharjo yang menyebabkan perubahan penggunaan lahan pertanian menjadi lahan terbangun secara masif. Penelitian ini bertujuan untuk mengidentifikasi perubahan penggunaan lahan pertanian menjadi lahan terbangun dan faktor yang menyebabkan terjadinya urban sprawl. Penelitian ini menerapkan metode penelitian deskriptif kuantitatif dengan pendekatan spasial, berupa overlay citra penggunaan lahan pada tahun 2017 dan 2025, serta analisis Geographically Weighted Regression (GWR). Hasil overlay menunjukkan adanya peningkatan lahan terbangun secara masif seluas 375,02 ha (37.95%). Hasil analisis GWR menunjukkan bahwa urban sprawl di lokasi kajian disebabkan oleh pertumbuhan jumlah penduduk, tingginya aksesibilitas, serta luasan lahan pertanian. Tekanan demografis memiliki dampak yang lebih signifikan terhadap konversi lahan di wilayah industri seperti Ceper. Sedangkan variabel aksesibilitas dan luas lahan pertanian memiliki pengaruh yang lebih kuat di Kecamatan Polanharjo dan Kecamatan Delanggu. Kata Kunci: Urban Sprawl, Perubahan Penggunaan Lahan, Faktor Penyebab